IMPACT OF ARTIST ELEMENT ON LOYALTY AND PURCHASE INTENTION CONSUMER IN MUSIC INDUSTRY (CASE STUDY : BANDUNG-JAKARTA MUSICIAN) (The Indonesian Journal of Business Administration, 2019)
Nowadays, there are many musicians who want to represent their work and obtain the revenue and profitability from their product, either come from live concert ticket sales, physical product sales, digital product sales, live concert streaming sales, branding sales from endorsement, partnership and other product,  with variety of different music genres. The revenue and profitability come from loyalty and purchase intention of music enthusiast, either listener, musician, and manager as the consumer.This research is using quanitative and qualitative methods for processing the data. Quantitative method is used by instrumentation test such as validity and reliability, classic assumption test like normality, heteroscedasticity, multicollinearity, autocorrelation, hypothesis test such as t-test and path analysis. To determine the significant influence of independent variable to dependent variable, researcher divided into three model. Qualitative method is used by interviewing method, to obtain the confirmation from the result of data process.From the quantitative result, based on first model, researcher obtain that branding has significant influence to music enthusiast’s loyalty. On second model, researcher obtain that branding, live concert, and physical product have significant influence for music enthusiast’s purchase intention. On third model, music enthusiast’s loyalty has significant influence for music enthusiast’s purchase intention. According from the result of data process, researcher purposed several recommendations to the musician, manager of musician, and record label to develop their revenue and profitability.Keywords: Quantitative, qualitative, t-test, path analysis, musician